The Minute City: between theory and practicality in suburban landscapes - Khaled Alawadi; Rim Anabtawi; Ghalya Alshehhi (Sustainability: Science, Practice, & Policy)
The “Minute City” (MC) concept has gained momentum in sustainability discourse, advocating for a transition in urban layout and transportation toward functional redistribution. Although the concept has found acknowledgment in urban centers, its application in suburban areas remains a subject of ongoing debate. This research studies the application of the 15-MC within Dubai’s neighborhoods. It explores network connectivity between parks and residential plots in 25 of the emirate’s neighborhoods (14 central and 11 suburban). Time, distance, and pedestrian-route directness (PRD) were evaluation metrics. The results indicate that, on average, both urban and suburban network configurations offer walking distances and times to community parks that are deemed acceptable. Furthermore, a substantial proportion of the samples from Dubai exhibited favorable results in meeting the directness criteria, suggesting considerable effectiveness in network design. Nevertheless, it is imperative to underscore that the prevailing local conditions, characterized by elevated temperatures and inherent infrastructure limitations, necessitate a thorough reevaluation that goes beyond the limitations of the obtained PRD results.